Bleak House - Dickens, Charles; Edited and With An Introduction by Bradbury Nicola ; Original Illustrations by Browne Hablôt K. (London Penguin Books, 1996)
Bleak House, Dickens's most daring experiment in the narration of a complex plot, challenges the reader to make connections - between the fashionable and the outcast, the beautiful and the ugly, the powerful and the victims. Nowhere in Dickens's later novels is his attack on an uncaring society more imaginatively embodied, but nowhere either is the mixture of comedy and angry satire more deftly managed. Bleak House defies a single description. It is a mystery story, in which Esther Summerson discovers the truth about her birth and her unknown mother's tragic life. It is a murder story, which comes to a climax in a thrilling chase, led by one of the earliest detectives in English fiction, Inspector Bucket. And it is a fable about redemption, in which a bleak house is transformed by the resilience of human
Include Index and Notes.
Esther, the illegitimate child of Lady Dedlock and Captain Hawdon, is the ward of Mr. Jarndyce and lives with him at Bleak House.
Keywords: England--London -- Illegitimate children